The Improving Student’s Vocabulary through Rewriting English Song Lyric “The Shawn Mendes Foundation Playlist” - Laveresa, Bayu; Prabowo, AB; Ambarini, Ririn (Lingua Franca, 2024)
The research investigates the efficacy of using English song lyrics, specifically drawn from Shawn Mendes' album "The Shawn Mendes Foundation Playlist," to enhance vocabulary skills among tenth-grade students at SMA Negeri 1 Comal. Employing a quantitative experimental approach, the research involved 70 students divided into experimental and control groups, undergoing pre-tests and post-tests to gauge vocabulary improvement. Results indicated a significant enhancement in vocabulary scores among students in the experimental group exposed to the treatment of rewriting English song lyrics. Conversely, the control group exhibited mixed outcomes, with some students experiencing declines, while others maintained or slightly improved their scores. Despite encountered difficulties in comprehending song lyrics and articulating ideas, proposed solutions included frequent exposure to English songs and active engagement in predicting song meanings. The findings underscore the potential of utilizing song lyrics, particularly from popular albums, as a valuable pedagogical tool for fostering vocabulary development in English language learning settings, thus advocating for their integration into language curricula.